MANAJEMEN INDUSTRI PETERNAKAN LAYER - Devi Y.J.A. Moenek (Partner, 2017)
In the middle of the various economic pressure in the country, poultry farm sector remains able to survive. Chicken and eggs as products of poultry industry having relatively cheaper prices could survive in the situation. Nowadays, however, the poultry industries in the country are still dominated by foreign investors. A large number of local farms are now beginning to get eliminated. Whereas previously these local farms dominated most of the markets, but now become marginalized. This might be caused by lacking in the use of modern technologies that required big investment. Generally partnerships in Indonesia have the concept of contract farming between large livestock feed producers and livestock farmers. Government policy has been less prioritize the livestock industry, including the policy on animal feed, so the feed price is never stable at a certain counterpart.Keyword : Layer, livestock industry, government policy